Asthaxanthin Improves Aerobic Exercise Recovery Without Affecting Heat Tolerance in Humans - Fleischmann, Chen; Horowitz, Michal; Yanovich, Ran; Raz, Hany; Heled, Yuval (Frontiers in Sports and Active Living, 2019)
Objectives: To examine the supplementation effects of the xanthophyll carotenoid Astaxanthin on physical performance and exertional heat strain in humans. Design: A randomized double blind placebo controlled trial. Methods: Twenty two male participants (Age: 23.14 ± 3.5 y, height: 175 ± 6 cm, body mass: 69.6 ± 8.7 kg, % body fat: 16.8 ± 3.8) received placebo (PLA, n = 10) or Astaxanthin (ATX, n = 12) 12 mg/day Per os (P.O), for 30 days, and were tested pre and post-supplementation with a maximal oxygen uptake (VO2 Max) test and the heat tolerance test (HTT) (2 h walk at 40°C, 40% relative humidity (RH), 5 kph, 2% incline). NIH database registration no. NCT02088242. Gas exchange, Heart rate (HR), Relative perceived exertion (RPE), and blood lactate were measured during the VO2 Max test. Heart rate (HR), rectal (Trec), and skin (Tskin) temperatures, RPE, and sweat rate (SR) were monitored in the HTT. Serum heat shock protein 72 (HSP72), Creatine phospho-kinase (CPK), C-reactive protein (CRP), and lipid profile were measured before and after the test. Results: The rise in blood lactate caused by the VO2 Max test was significantly diminished in the ATX group (9.4 ± 3.1 and 13.0 ± 3.1 mmole*l−1 in the ATX and PLA groups, respectively P < 0.02), as was the change in oxygen uptake during recovery (−2.02 ± 0.64 and 0.83 ± 0.79% of VO2 Max in the ATX and PLA group, respectively, p = 0.001). No significant differences were observed in the anaerobic threshold or VO2 Max. In the HTT, no significant physiological or biochemical differences were observed (HR <120 bpm, Trec rose by 1°C to <38°C, no difference in SR). Conclusions: Astaxanthin supplementation improved exercise recovery. No benefit was observed for ATX over PLA in response to heat stress. Further examination of Astaxanthin in higher exertional heat strain is required.